2015
DOI: 10.1017/s0954102015000127
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of recent lacustrine sediments from Fildes Peninsula, King George Island, maritime Antarctica

Abstract: Comprehensive geochemical analyses (bulk parameters, major and trace elements, organic matter, mineralogy and particle analysis) were carried out on sediments from seven lakes on Fildes Peninsula, King George Island. The resulting compositional dataset was subjected to principal component analysis and cluster analysis. The results showed that four different lacustrine sedimentary environments can be distinguished: i) lakes 1 and 2 with relatively high values of secondary aluminous clay minerals, ii) lake 4 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 34 publications
(37 reference statements)
4
6
0
Order By: Relevance
“…Minerals such as quartz, zeolite, plagioclase and magnetite present solution pits, precipitation coatings and dissolution etching, all comprising alteration products of chemical weathering of source rock during contact with external factors, presumably present at the time of ice withdrawal when source rock was exposed to the atmosphere and biosphere. This type of chemical alteration of minerals was previously reported in lacustrine sediment from the Fildes Peninsula by Alfonso et al (2015). Alternatively, such weathering may be linked to one or more interglacial periods of the Pleistocene prior to ice readvance, bedrock release, entrainment and transport, with grain overprinting to the lake.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Minerals such as quartz, zeolite, plagioclase and magnetite present solution pits, precipitation coatings and dissolution etching, all comprising alteration products of chemical weathering of source rock during contact with external factors, presumably present at the time of ice withdrawal when source rock was exposed to the atmosphere and biosphere. This type of chemical alteration of minerals was previously reported in lacustrine sediment from the Fildes Peninsula by Alfonso et al (2015). Alternatively, such weathering may be linked to one or more interglacial periods of the Pleistocene prior to ice readvance, bedrock release, entrainment and transport, with grain overprinting to the lake.…”
Section: Discussionsupporting
confidence: 61%
“…In the Canadian Soil Classification System, these pedons would key out as Regosols (Soi1 Classification Working Group 1998). In addition, geochemical studies of lacustrine sediment from Fildes Peninsula indicate that local bedrock is probably the main source of sediment in Profound Lake, which contrasts with other nearby lakes that have high concentrations of some elements (Ba, Sr, P) and zeolites (Alfonso et al 2015). Using geochemical data from local bedrock of King George Island, Monien et al (2011) showed that short-term alterations in the regional climate during the last ca.…”
Section: Geological Settingmentioning
confidence: 99%
“…Lacustrine sediments carry a strong signal originating from minerogenic and chemical weathering products of the catchment areas (i.e. solutes and particulate material) and can be considered to be representatives of sedimentological and biogeochemical processes taking place in the watershed (Alfonso et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the cluster analysis, Ward, Simple and Paired methods were employed. Euclidean distance was used for the distance measure (ALFONSO et al, 2015). For the Principal Component Analysis, the correlation coeffi cient was used as the initial matrix of similarities, to eliminate the eff ect of scale.…”
Section: Methodsmentioning
confidence: 99%